Orbital ameloblastoma: research and challenges of a rare benign tumor - Rui Zhang; Xiaoming Huang; Fengyuan Sun; Tong Wu (Holistic Integrative Oncology)
Abstract There are numerous types of orbital tumors, among which orbital ameloblastoma is a rare metastatic benign tumor that often originates in the jaw and later metastasizes to the orbit. The mystery of it lies in that, although it is classified as a benign tumor, it exhibits high recurrence and malignant potential with high invasiveness, posing a serious threat to ocular health and the quality of life of patients. The prognosis of orbital ameloblastoma is relatively poor, but there is still hope. With aggressive treatment and close follow-up observation, patients may still have the possibility of achieving a longer survival period and a better quality of life. The global incidence of ameloblastoma is 0.92 cases per million people per year. According to world literature reports, there are 32 cases of maxillary bone metastasis to the orbit and 4 cases of mandibular bone metastasis to the orbit. With more and more cases and related research being reported, it is necessary to comprehensively review the etiology, clinical manifestations, diagnosis, treatment, and prognosis of orbital ameloblastoma, in order to enhance ophthalmologists' understanding and diagnostic and treatment skills of this disease, and ultimately improve patients' prognosis and quality of life.